Integrasi Ilmu Agama dan Sain dalam Praksis Pendidikan - M Nafiur Rafiq (FALASIFA : Jurnal Studi Keislaman, 2017)
Until now still strong assumption in the wider community that says that "religion" and "science" are two entities that can not be reconciled. Both have their own territory, separated from one another, both in terms of material-formal objects, research methods, truth criteria, roles played by scientists as well as their theoretical status even to the institution of the organizers. That is a picture of education praxis and scientific activities and learning in the homeland so far with a variety of negative impacts caused by the wider community. To end the praxis of scientific dichotomy in the world of education, it is necessary to develop patterns or learning tips that are integrated in each type and level of educational institutions in Indonesia both formal and nonformal. The main key in implementing the development of scientific integration in this educational process lies in the competence of educators and curriculum, adequate facilities and infrastructure and management of educational institutions themselves.Keyword: Integrasi, Ilmu Agama dan Sain, Praksis Pendidikan.